Observation of high-energy neutrinos from the Galactic plane - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
IceCube has discovered a flux of astrophysical neutrinos and presented evidence for the first neutrino sources, a flaring blazar known as TXS 0506+056 and the active galaxy NGC 1068. However, the sources responsible for the majority of the astrophysical neutrino flux remain elusive. In addition to hypothetical sources within our Galaxy, high energy neutrinos are produced when cosmic rays interact at their acceleration sites and during propagation through the interstellar medium. The Galactic plane has therefore long been hypothesized as a neutrino source. In this contribution, new results are presented for searches of neutrino sources utilizing a dataset that builds upon recent advances in deep-learning-based reconstruction methods for neutrino-induced cascades. This work presents the first observation of high-energy neutrinos from the Milky Way Galaxy, rejecting the background-only hypothesis at 4.5 σ. The neutrino signal is consistent with diffuse emission from the Galactic plane, potentially in combination with emission by a population of sources.
CRIS-Team Scopus Importer:2025-02-04